The 10-year Trend of TB Rate in West Azerbaijan Province, Iran from 2001 to 2010 - RAHIMI FOROUSHANI, Abbas (Iran J Public Health, 2014)
BACKGROUND: The present study aimed to explore some risk factors affected the mean of the number of tuberculosis (TB) in West Azerbaijan Province, Iran between 2001 and 2010. METHODS: Our time series study analyzed the data of 2,560 TB patients as registered with TB Patients Care System in West Azerbaijan Province from early 2001 to 2010. A checklist was prepared for collecting the data and they were then analyzed in SPSS V.16 software. RESULTS: The percentage of male and percentage of female were close to each other (52.2% against 47.8%, respectively). A significant increasing trend of TB rate was found over the years of 2001and 2010 with a pick at 2008 (P<0.001). A Poisson log-linear analysis showed that the most important risk factor of the trend of rate was the level of education so that people with primary level or with illiterate level had a statistically significant TB rate of 5.21 (4.66-5.81), adjusted for years. The next risk factor was type of TB and place of residency, i.e., pulmonary TB cases had higher rate than External pulmonary TB cases (RR=1.67; (1.54-1.80). The last factor with the lowest risk was BCG with RR=1.29 (1.20-1.40) for people who received BCG compared to the people who had not received it. CONCLUSION: Although the co morbidity of AIDS and TB was not a major problem, it is necessary that special attention be paid to the way of implementing the TB control program based on the demographic risk factors of the study population.